Analisis Dimensions dengan Keyword Takhrij Hadis menggunakan Teknik Bibliometrik - Ina Nurseha (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the dimensions with the keyword takhrij hadith. This study uses a bibliometric dimensions technique. The formal object of this research is dimensions, while the material object is dimensions analysis with the keyword takhrij hadith. The results and discussion of this study indicate that there are four categories in the takhrij hadith mapping research. First, the research category in the publication of articles on takhrij hadith. Second, the development of publications (overview) regarding takhrij hadith. Third, researchers who play an active role in takhrij hadith. And fourth, the place of publication that dominates publications regarding takhrij hadith.